Bakti Sosial Peduli Pendidikan Sebagai Bentuk Pengabdian Kepada Masyarakat di Desa Ciwarna Mancak Kabupaten Serang - Riska Ferdiana; Intan Indria Dewi; Irwan Sukmawan; Kenedi Kenedi; April Laksana (WINDRADI: Jurnal Pengabdian Masyarakat, 2023)
The community service programs implemented cover various aspects of community life, such as education, environment, economics and social. Building the capacity and empowerment of the Ciwarna Village community is also the main focus, by providing assistance and providing relevant assistance. In conclusion, SENABUNG's synergy in social activities with Bina Bangsa University KKM students in Ciwarna village has an important role in improving the quality of life of the local community. This collaboration reflects the spirit of cooperation and commitment of universities and students to actively contribute to solving social problems and improving community welfare